1995
DOI: 10.3177/jnsv.41.187
|View full text |Cite
|
Sign up to set email alerts
|

Antihypercholesterolemic Effect of Undigested Fraction of Soybean Protein in Young Female Volunteers.

Abstract: SummaryThe significant antihypercholesterolemic effect of the un digested high molecular fraction (HMF) of soybean protein is known in rats, but such an effect has not been shown in humans. The present two experiments were designed to elucidate it in humans. Subjects were female university students who had relatively high serum cholesterol levels for their age. In Experiment 1, subjects took 8% of their total energy from casein, soybean protein isolate (SPI), or HMF daily for 14 days. Five basic menus and snac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0
3

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 22 publications
1
24
0
3
Order By: Relevance
“…Sugano et al (37) have shown that in rats fed soybean protein, the undigested peptide fraction produced in the lumen binds steroids and is excreted into stool, resulting in the decrease of serum cholesterol level. We (38) confirmed their results in hypercho lesterolemic women. We (39) have shown that a small quantity (about 0.1%) of peptides produced in the lumen from protein are absorbed intact and appear in the circulatory system, and that they show various functions, e.g.…”
Section: Discussionsupporting
confidence: 86%
“…Sugano et al (37) have shown that in rats fed soybean protein, the undigested peptide fraction produced in the lumen binds steroids and is excreted into stool, resulting in the decrease of serum cholesterol level. We (38) confirmed their results in hypercho lesterolemic women. We (39) have shown that a small quantity (about 0.1%) of peptides produced in the lumen from protein are absorbed intact and appear in the circulatory system, and that they show various functions, e.g.…”
Section: Discussionsupporting
confidence: 86%
“…8) Sugano and his coworkers digested a soy protein isolate in vitro by microbial proteases and prepared soluble and residual fractions, these being referred to as the low-molecular fraction (LMF) and high-molecular fraction (HMF), respectively. 9) They examined their cholesterol-lowering effect on an animal model [9][10][11] as well as on human volunteers 12) and found that HMF caused higher fecal excretion of the steroids and consequently had a cholesterol-lowering effect in the serum than the intact soy protein isolate. They speculated from the results that specific peptide fragments rich in HMF would exert this cholesterol-lowering effect through interference with the steroid-absorption process.…”
mentioning
confidence: 99%
“…[1][2][3] It has also been reported that HMF increases fecal steroid excretion and reduces the serum cholesterol level in humans. 4) Resistant proteins (RPs), which are indigestible remnants of dietary proteins, have recently been acknowledged to function like plant-derived dietary fibers in the intestine. 5) We have previously estimated that 25-30% of HMF was excreted into feces as undigested remnant.…”
mentioning
confidence: 99%